2010
DOI: 10.22146/gamaijb.5516
|View full text |Cite
|
Sign up to set email alerts
|

The Importance and Usefulness of Corporate Annual Reports in Malaysia

Abstract: The purpose of this study is to examine the perceived importance and usefulness of corporate annual reports in Malaysia and to determine if there is a difference between the perceptions of preparers and users of corporate annual reports. Data for this study were collected using a questionnaire survey conducted in late 2006 and early 2007. Preparers are represented by chief financial officers while users by investment analysts. The mean scores for preparers and users are compared using the independent samples t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 21 publications
(48 reference statements)
0
4
0
Order By: Relevance
“…Apart from numbers, analysis is made based on the information from the annual report and takes into account historical and present data. A study concluded that analysis on annual reports assist its readers in comparing performances among companies (Ghazali, 2010). Another study has also deduced that by reading the narrative section of annual reports or financial statements, one could gain knowledge on the performance of an organization (Brown & Whittington, 2007).…”
Section: Financial Statement Analysismentioning
confidence: 99%
“…Apart from numbers, analysis is made based on the information from the annual report and takes into account historical and present data. A study concluded that analysis on annual reports assist its readers in comparing performances among companies (Ghazali, 2010). Another study has also deduced that by reading the narrative section of annual reports or financial statements, one could gain knowledge on the performance of an organization (Brown & Whittington, 2007).…”
Section: Financial Statement Analysismentioning
confidence: 99%
“…The regulation of Malaysian companies' financial reporting is prescribed by the Companies Act 2016, the MFRS and the Bursa Malaysia listing requirements. Ghazali (2010) investigated the importance and usefulness of corporate annual reports in Malaysia and the difference in perceptions between users and preparers. Findings from the study are that the preparers (chief financial officers) of the annual report rank the annual report as the most important source of corporate information; while users (investment analysts) rank the annual report as the second most important after visit to companies as the users need to have more timely and relevant information about the company (Ghazali, 2010).…”
Section: Users' Perceptions Of Annual Reportsmentioning
confidence: 99%
“…Ghazali (2010) investigated the importance and usefulness of corporate annual reports in Malaysia and the difference in perceptions between users and preparers. Findings from the study are that the preparers (chief financial officers) of the annual report rank the annual report as the most important source of corporate information; while users (investment analysts) rank the annual report as the second most important after visit to companies as the users need to have more timely and relevant information about the company (Ghazali, 2010). In addition, they found that annual reports help the users to evaluate a company's performance while for the preparers, they feel that the annual report is useful to them to compare performance of companies.…”
Section: Users' Perceptions Of Annual Reportsmentioning
confidence: 99%
“…Despite the above lacuna, companies disclose human resource information to their stakeholders in the annual report. This is because when it comes to making investment decisions, stakeholders place a high value on the annual report (Ghazali, 2010;Anderson, 1981;Chang et al, 1983). Companies are motivated to reveal human capital (HC) data to build employee and stakeholder confidence (Prusak & Cohen, 2001;Backhaus et al, 2002).…”
Section: Introductionmentioning
confidence: 99%